Case Series: Myelin Oligodendrocyte Glycoprotein-Immunoglobulin G-Related Disease Spectrum - Alshamrani, Foziah; Alnajashi, Hind; Shosha, Eslam; Casserly, Courtney; Morrow, Sarah A. (Frontiers in Neurology, 2020)
Introduction: Myelin oligodendrocyte glycoprotein-immunoglobulin G (MOG-IgG)-related disease was initially described as a subtype of neuromyelitis optica spectrum disorder (NMOSD) with antibodies against MOG. However, it has recently been described as a separate disease entity with clinical and radiological features that overlap those of multiple sclerosis (MS) and NMOSD; the clinical features of this disease phenotype remain undetermined. We herein report the clinical presentation of nine MOG-IgG-positive patients, not all of whom fulfill the NMOSD criteria, in order to highlight the features and challenges of this condition. Method: We retrospectively reviewed the records of the London (Ontario) MS clinic to identify patients diagnosed with positive MOG antibodies based on the 2015 NMOSD consensus criteria. Result: Nine patients were identified, all Caucasian. Seven (78%) were female, and the median age of onset was 41 years (range, 28-69 years) and the median Expanded Disability Status Scale score at onset was 3.0 (range, 2.0-4.0). A monophasic course was noted in two (22.2%) patients, while the median number of relapse events was 3 (range 2-5) in 77.8% patients. Optic neuritis and transverse myelitis contributed equally as initial manifestations in three individuals (33%), while brainstem relapse was reported in two individuals (22%). The brain magnetic resonance imaging findings were compatible with McDonald’s 2010 dissemination in space criteria in three cases (33%). Short myelitis and an (H)-sign were each documented in one patient. Conclusion: The phenotypes of MOG Ab-positive cases exhibited overlapping features with MS and NMOSD. This finding highlights the importance of screening for anti-MOG in individuals with demyelinating symptoms, in consideration of the possibility of false positive MOG Ab results.